Effect of hypnosis on anxiety and blood pressure of pregnant women with preeclampsia: A double-blind controlled clinical trial study - Farzaneh Seitz; Mehdi Pourasghar; Abolfazl Hosseinnataj; Seydeh Zeynab Hoseinnezhad; Nooshin Eshraghi; Jila Ganji (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The risk is on the level of blood pressure, and blood pressure is one of the prominent characteristics of preeclampsia. The aim of this study is to assess the effect of hypnosis on the pressure and blood pressure of pregnant women with preeclampsia. MATERIALS AND METHODS: In this controlled clinical trial study, 44 pregnant women from 20 to 32 weeks referred to Shahid Akbarabadi Hospital in Tehran in 2022 were randomly assigned to two intervention and control groups. Hypnotherapy was conducted individually and online for five sessions. Evaluation of performance and blood pressure (primary outcome) was done using the DASS-21 questionnaire and sphygmomanometer before, during maintenance, and 4 weeks after the intervention. Twenty people in each group entered the analysis stage. Independent t-test, Chi-square, analysis of variance with repeated measures and mixed model were used, and effect size (Cohen's D) was used to evaluate the strength of the intervention effect. The data were entered into the SPSS software version 22 and a significance level of 0.05 was considered. RESULTS: The results showed that the two groups did not differ in terms of background changes (P = 0.757). The score after the intervention decreased by 10.25 (P < 0.001) and the time 1 month after the intervention decreased by 9.93 (P < 0.001). The blood pressure after the intervention was reduced by 7.90 (P < 0.001) and the blood pressure 1 month after the intervention by 7.52 (P < 0.001). CONCLUSION: It is suggested to use hypnotherapy as a complementary treatment to reduce anxiety and preeclampsia symptoms.